South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper estimates the potential growth rate for South Africa using different methodologies. In line with existing studies and findings for other emerging markets, the paper finds that South Africa's potential growth rate has declined in the post global financial crisis period. Though there is substantial uncertainty, South Africa's potential growth is estimated to have fallen from an average of 3.5 to 4 percent during 2000-08 to 2.25 to 2.50 percent in 2010-14, implying that the output gap in 2014 would be between -0.5 and -1.3 percent of GDP.